DCAF: Dynamic Cross-Chain Anchoring Framework using Smart Contracts. (8th May 2021) - Wang, Weidong; Li, Xiaofeng; Zhao, He
Abstract: Blockchain has attracted tremendous attention from both the academia and the capital market. The insertion of data in a blockchain known as anchoring makes data verifiable and independently auditable and has many potential applications. The objective of this paper is to introduce a dynamic cross-chain anchoring framework for snapshotting users' data into multiple public blockchains with the help of smart contracts. This paper starts by proposing the framework and depicting the components and workflow. Second, we design a target chain selection algorithm that combines the states of different blockchains. Using the algorithm, users can dynamically select a suitable public blockchain for anchoring tasks. Third, the virtual chain protocol is presented and achieves data anchoring orderly and integrally. Analyzation and evaluation show that the framework can enhance user experience, robustness and performance.